Smartdesa Application for Hamparan Perak Village Using Crowdsourcing for Community Reporting - Tambunan, Salwa Alipia Fadillah; Alda, Muhamad (Journal of Information System and Informatics, 2025)
The development of digital technology presents opportunities to improve public services at the village level. Hamparan Perak Village faces challenges in delivering information, which still relies on bulletin boards, long wait times at the village office for mail administration and limited communication channels for residents to submit reports or complaints. To address these challenges, the multiplatform Smartdesa application was developed with a crowdsourcing reporting feature. Residents can submit reports and vote on other reports to prioritize their handling. The application was built using React Native for Android and Next.js for the web admin system, with Express.js as the backend, MySQL as the database, and JavaScript as the programming language. Testing results show that the application accelerates report processing and encourages active community participation in digital village management. Several obstacles were also identified, such as limited digital literacy among some users and sometimes unstable internet connections. Nevertheless, the Smartdesa application shows great potential for implementation in other villages as part of e-Government or smart village initiatives.